(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper is an inquiry of the experience of PhD students in Islamabad as women, in what way the gendered domestic expectations interact with the academic demands of a competitive system of higher education. Based on the Role Theory and Social Constructionism, the study explores the various social roles, culturally produced norms, and institutional expectations from PhD scholars. In-depth semi-structured interviews of five female PhD students of various disciplines, marital status, and family arrangement were done using a qualitative research design. Thematic analysis identified five key themes namely, gendered domestic expectations and role conflict, academic pressure and gendered expectations, psychological strain and emotional burden, and intersectionality of gender, family, and academic constraints, and strategies and support systems. The results point to the fact that domestic roles, social values, and organizational frameworks affect female academics out of proportion, exacerbating role stressors and psychological issues. Various coping strategies are adopted by the participants, such as careful time management, peer support, and the allocation of family responsibilities, but there is the lack of institutional support. The research advances the knowledge of gendered aspects of doctoral education in Pakistan and highlights the necessity of the family-friendly policies, gender-sensitive supervision, and culturally sensitive interventions to foster the well-being and academic performance of female students.